DESIGN AND EXPERIMENTAL STUDY OF LAMB WAVE BASED ACTIVE STRUCTURAL HEALTH MONITORING SYSTEM ON QUASI-ISOTOPIC GFRP PLATE - Hamzah Farrasamulya, Muhammad
Lamb wave based Structural Health Monitoring (SHM) system has the ability to detect delamination in plate-like structure made of composite. This system can potentially detect damage in the early stage hence enables the use of composite materials with smaller safety margin in a structure. This thesis presents a study on the development of an active sensing Lamb wave based SHM system. Two thin quasi-isotropic Glass Fiber Reinforced Polymer (GFRP) plates were used as specimens, one represents a healthy plate and the other one with a small circular metallic insert represents a plate with a delamination. An array of piezoelectric (PZT) transducers were mounted on each plate. Experiments were carried out by using one transducer as a pulse actuator and one other transducer as sensor, repeated for several actuator-sensor pairs. A signal processing based on Hilbert Transformation and auto-correlation calcu- lation is then used to analyze the signals measured by sensor on the damaged plate and compare it to that of the healthy plate to obtain the time of flight (TOF) of damage-re ected wave. Based on this TOF value, an ellipse-shaped possible locus of the damage relative to the actuatorsensor path can be calcu- lated. A data fusion and imaging algorithm was then used to show the location of predicted damage which is determined by the largest amount of damage lo- cus intersections created by pairs of actuator-sensor employed. The results show that the developed procedure is able to locate the center of damage with relatively small deviation.